The importance of the electronic and steric features of the ancillary ligands on the rate of cis–trans isomerization of olefins coordinated to palladium(0) centre. A study involving (Z)-1, 2-ditosylethene as olefin model. (15th November 2019) - Scattolin, Thomas; Canovese, Luciano; Demitri, Nicola; Santo, Claudio; Visentin, Fabiano
Graphical abstract: With the aim of better understanding the mechanisms governing the spontaneous cis – trans isomerization of the olefins promoted by palladium(0) centers, we have synthesized several novel complexes bearing (Z)- or (E)-1, 2-ditosylethene and a combination of other two spectator ligands including phosphines (PPh3 and 1, 3, 5-triaza-7-phosphaadamantane), isocyanides (i.e. 2, 6-dimethylphenylisocyanide) and N -heterocyclic carbenes (NHCs). Abstract: With the aim of better understanding the mechanisms governing the spontaneous cis – trans isomerization of the olefins promoted by palladium(0) centers, we have synthesized several novel complexes bearing (Z)- or (E)-1, 2-ditosylethene and a combination of other two spectator ligands including phosphines (PPh3 and 1, 3, 5-triaza-7-phosphaadamantane), isocyanides (i.e. 2, 6-dimethylphenylisocyanide) and N -heterocyclic carbenes (NHCs). The nature of ancillary ligands heavily influences the steric and electronic features of the metal centre and consequently its interaction with olefin determines a different capability of supporting the isomerization process. The kinetic analysis and the determination of the rate constants of the isomerization suggested that both the steric and electronic factors play an important role and only an unpredictable combination can guarantee the success of the reaction. The work is completed by the structural characterization of three different Pd(0) complexes.